2003
DOI: 10.1016/s0378-1097(03)00513-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of metronidazole-resistance by isolates of nitroreductase-producingEnterococcus gallinarumandEnterococcus casseliflavusfrom the human intestinal tract

Abstract: Enterococcus casseliflavus and Enterococcus gallinarum strains resistant to metronidazole, nitrofurantoin and nitrofurazone were isolated from fecal samples of a patient with recurrent ulcerative colitis treated with metronidazole. Unlike other metronidazole-resistant bacteria, these strains produced nitroreductase but metabolized metronidazole to compounds that could not be detected by liquid chromatography with UV or mass spectral analysis. Metronidazole-susceptible Clostridium perfringens grew equally well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…Previous studies have found that Enterococcus is often enriched in the nitroaromatic nitrobenzene-reducing biocathode communities, and the relative abundance can reach 38.4% or 74.7% (Wang et al, 2011). This was consistent with the fact that Enterococcus and Pseudomonas species own nitroaromaticsreducing ability (Rafii et al, 2003;Roldan et al, 2008). These results indicated that the microbial community structure with applied electrical stimulation was obviously different from that of the open circuit biofilm.…”
Section: Potential Function Of Dominant Generasupporting
confidence: 79%
“…Previous studies have found that Enterococcus is often enriched in the nitroaromatic nitrobenzene-reducing biocathode communities, and the relative abundance can reach 38.4% or 74.7% (Wang et al, 2011). This was consistent with the fact that Enterococcus and Pseudomonas species own nitroaromaticsreducing ability (Rafii et al, 2003;Roldan et al, 2008). These results indicated that the microbial community structure with applied electrical stimulation was obviously different from that of the open circuit biofilm.…”
Section: Potential Function Of Dominant Generasupporting
confidence: 79%
“…1B). This inability to recover metronidazole has been previously noted (18), and it has been suggested that inactivation of metronidazole by human gut microbiota such as enterococci may be responsible for the lack of activity (19,20).…”
Section: Resultsmentioning
confidence: 84%
“…For example, Dysgonomonas and Escherichia could ferment glucose with production of volatile acid under facultative anaerobic conditions were enriched in the initial inoculum. Enterococcus (38.42%) and Raoultella (11.09%) dominated in the gBC attributed to they could reduce nitroaromatics into corresponding aromatic amines under heterotrophic cultivation (Claus et al, 2006;Rafii et al, 2003). …”
Section: Potential Function Of Dominant Generamentioning
confidence: 99%